2006
DOI: 10.1113/expphysiol.2006.034439
|View full text |Cite
|
Sign up to set email alerts
|

Colitis‐induced oxidative damage of the colon and skeletal muscle is ameliorated by regular exercise in rats: the anxiolytic role of exercise

Abstract: Epidemiological studies have shown that exercise protects the gastrointestinal tract, reducing the risk of diverticulosis, gastrointestinal haemorrhage and inflammatory bowel disease, while many digestive complaints occurring during exercise are attributed to the adverse effects of exercise on the colon. In order to assess the effects of regular exercise on the pathogenesis of colitis, Sprague-Dawley rats of both sexes were either kept sedentary or given exercise on a running wheel (0.4 km h −1 , 30 min for 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
25
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 56 publications
6
25
0
2
Order By: Relevance
“…In patients with duodenal ulcer, combining the conventional antiulcer treatment with bicycle exercise has accelerated the healing of ulcer [37]. Similarly, we have previously shown in rats that colonic damage induced by acetic acid was improved by regular exercise [38]. The current data also demonstrate that exercising regularly prior to the occurrence of ulcer has a protective and a healing-accelerating effect on acetic acidinduced oxidative damage.…”
Section: Discussionsupporting
confidence: 67%
“…In patients with duodenal ulcer, combining the conventional antiulcer treatment with bicycle exercise has accelerated the healing of ulcer [37]. Similarly, we have previously shown in rats that colonic damage induced by acetic acid was improved by regular exercise [38]. The current data also demonstrate that exercising regularly prior to the occurrence of ulcer has a protective and a healing-accelerating effect on acetic acidinduced oxidative damage.…”
Section: Discussionsupporting
confidence: 67%
“…colonic oxidative insult in a rat model of colitis. 32 Of course, prolonged excessive exercise has a deleterious influence on intestinal function. Intense exercise redistributes blood from the splanchnic circulation to actively respiring tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Szalai et al [62] also found evidence of benefit from recreational levels of exercise (wheel-running) in rats with TNBS-induced colitis in terms of decreased pro-inflammatory genes, the induction of antiinflammatory mediators, and modulation of the activity of HO and NOS enzymes. A controlled study of rats with an acetic acidinduced colitis confirmed that 6 weeks of moderate exercise on a running wheel (0.4 km/h, for 30 min, 3 days/wk) reduced markers of oxidative stress, and histological damage to the colon, in association with a reduction of stress as assessed by holeboard tests [32]. Saxena et al [57] evaluated adiponectin-defi- [54] 15 paediatric cases of CD in remission 30 min cycling at 50 % peak power or 6 bouts of 4 × 15 s cycling at 100 % peak power 16 of 20 subjects completed exercise protocols Robinson et al [55] 117 cases of CD randomized to low impact exercise or control group 12 low-impact floor exercises, 2/wk for 12 months 85 % completed programme, only 25 % followed prescribed regimen CD = Crohn's disease; CIBD = inflammatory bowel disease; ns = non-significant; UC = ulcerative colitis Patients show low IGF-1 and high IL-6 CD = Crohn's disease; HBI = Harvey-Bradshaw Index; CIBD = Inflammatory Bowel disease; IBDQ = Inflammatory bowel disease questionnaire; IBS = irritable bowel syndrome; IGF-1 = insulin-like growth factor 1; IL-6 = interleukin 6; 1RM = 1 repetition maximum; PA = physical activity; RR = risk ratio; TNF-α; tumour necrosis factor alpha; UC = ulcerative colitis…”
Section: Endocrine and Immune Functionmentioning
confidence: 99%